DINAMIKA KEMUNGKINAN PERUBAHAN STATUS MENJADI DESA DI KELURAHAN CIMAHPAR KECAMATAN BOGOR UTARA KOTA BOGOR - Andi Azikin (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2018)
Villages that have a very strategic role and position in national development and resilience because most of the Indonesian people are in the countryside. Realizing a strong village will directly affect the realization of regional autonomy because the village government is the leading unit in the service to the community and becomes strategic for the success of governance. With the issuance of Law No. 6 of 2014 concerning Village, opening up space for changes in status and institutions, changes in the status of village-kelurahan or vice versa, villages which have implications for the institutional dynamics of government in the villageChanges in the implementation of village governance are manifested in changes in the institutions of the village government - villages that have different service behaviors. Meanwhile, the phenomenon of changes in village governance still leaves the dynamics of the current village government institutions, whether the village government is a community comunity organization that carries out government functions or basic government is an autonomous region as part of the system and structure of governance in Indonesia. It is different with the position of the Kalurahan as a more stable area of urban society, because the village is an institution of regional government as part of the District Device Organization (Government Regulation No. 18 of 2016 concerning regional apparatus article 52), which is authorized to carry out government activities, empowerment community and provide community services in order to assist or carry out some of the tasks of the camat